Financial Improvement of PT Adhi Karya (Persero) Tbk to Complete in ASEAN Construction Industry - Wibisana, Yudha Nugraha; Damayanti, Sylviana Maya (Journal of Business and Management, 2016)
Abstract â€“ In 2016, Asean Economic Community (AEC) will effectively begin. The purpose of this international collaboration is to enforce economic power in South-East Asia region to become single market and production base. However with policies that may apply according to AEC agreements, there will be challenges for each country in South East Asia region especially because of the tighter competition that might occur. The purpose of this research is to see the readiness of national company to compete in Asean level and to give recommendations to companyâ€™s future improvement.. Author chooses PT Adhi Karya (Persero) Tbk. as the object of this research because they have statement in their vision to become the leading company in South East Asia. Moreover, PT Adhi Karya (Persero) Tbk is a company that involved in the industry of construction, one of the most strategically critical industries in developing country like Indonesia. To assess the readiness of PT Adhi Karya (Persero) Tbk., author use analysis of financial ratios to determine the current financial performance of the company. In addition, author also use BUMN framework scoring to get more information about company financial performance. As a benchmark, 3 companies in Indonesia and 3 companies from foreign country in Asean region. The analysis shown that PT Adhi Karya (Persero) Tbk. have many rooms to improve in their current financial performance. The company needs to increase their efficiency. Currently they need averagely 65 days to collect their receivables, which is considerably too long. The company also has to utilize their asset more efficiently since the findings shown that their significant increase in asset did not followed by high increase on sales. For leverage, PT Adhi Karya (Persero) Tbk could increase their debt to increase their financial leverage. They also could considering to merger or joint venture with foreign company from South-East Asia to prepare the competition of AEC since there are some foreign companies that perform well in construction industry,Â Keywords: Finance, financial performance, financial ratio analysis, construction industry, state-owned enterprises, Asean Region.